Measuring nanoparticle-induced resonance energy transfer effect by electrogenerated chemiluminescent reactions. Issue 7 (23rd January 2020) - Perez-Tejeda, Pilar; Martínez-Delgado, Alberto; Grueso, Elia; Giráldez-Pérez, Rosa M.
Abstract : Electrogenerated chemiluminescence efficiencies, redox potentials, photoluminescent (quenching and coupling) effects, and AFM images for the [Ru(bpy)3 ] 2+ /Au@tiopronin system were determined in aqueous solutions of the gold nanoparticles at pH 7.0. Abstract : Electrogenerated chemiluminescence (ECL) efficiencies, redox potentials, photoluminescent (PL) (quenching and coupling) effects, and AFM images for the [Ru(bpy)3 ] 2+ /Au@tiopronin system were determined in aqueous solutions of the gold nanoparticles (NPs) at pH 7.0. The most remarkable finding was that ECL measurements can display the nanoparticle-induced resonance energy transfer (NP-RET) effect. Its effectiveness was quantified through a coefficient, K (NP-RET)ECL, which measures how much an ECL reaction has been enhanced. Moreover, the NP-RET effect was also checked using PL measurements, in such a way that a coefficient, K (NP-RET)PL, was determined; both constants, K (NP-RET)ECL and K (NP-RET)PL being in close agreement. It is important to highlight the fact that the NP-RET effect is only displayed in diluted solutions in which there is no NPs self-aggregation. The existence of the NPs self-aggregation behavior is revealed through AFM measurements.